The Chakri Dynasty’s “Open Door” Policy in Nineteenth Century: The Background of International Intergration Of the Modern Thailand - Van Chuong, Dang (KnE Social Sciences, 2017)
In order to protect Thailand’s independence and sovereignty under the strong pressures of the western powerful nations, Kings of the early Chakri dynasty had the determination to conduct a change from “close door” policy to “open door” policy. It was conducted under the reigns of King Rama IV and Rama V in the middle of nineteenth century. This was not only a new policy but it also became its pioneer in Asia. This “open door” policy was not only to protect Thailand’s independence but also to develop its economy and society. On the basis of economy and society reforms, Thailand government had implemented the reforms on the politics: turning absolute monarchy into constitutional monarchy. All this helped Thailand to hold a new position in the international relations. Thailand became a nation which had equal position with other nations. It allowed Thailand to integrate with international community, and became a nation which had the first position in the Southeast Asia in the first half of the twentieth. Keywords: “Open door” policy, “Close door” policy, Chakri dynasty, Independence, reform, diplomat, Thailand